To your eternity. 16 - Ōima, Yoshitoki (Ōima, Yoshitoki. Fumetsu no anata e., 2022)
"Now, the Nokkers lurk just beneath the surface at school, at playgrounds, and even within Fushi's friend circle. As Mizuha's family secret comes to the fore, the Nokkers stretch their tendrils toward the Beholder, who has been reborn as a human boy named Satoru."--Back cover.